Effects of feeding oats or oat hulls and meal or pellets on the performance of weanling pigs - A J Thulin; G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1979)
Two hundred fifty eight, five-week old weanling pigs were used to evaluate various levels of dietary oats and oat hulls in swine diets by performance and incidence of diarrhea in pigs weaned at approximately 5 to 6 weeks of age (17.6 to 28.6 lbs.).; Swine Day, Manhattan, KS, November 8, 1979
Keywords: Swine day; 1979; Kansas Agricultural Experiment Station contribution; no. 80-136-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 371; Swine; Oats; Oat hulls; Pellets; Performance; Weanling pigs